Genetic visualization of cultural heritage: A case study of Zhuxian Town woodblock prints - Liu, Haoran; Alli, Hassan; Md Yusoff, Irwan Syah (Taylor and Francis, 2024)
Using genetic visualization technology to effectively convey cultural information plays an important role in preserving cultural heritage. The key to preserving and developing cultural ecology levels is employing visualization methods and a strategic approach. A valuable tool for conservation, restoration, and cultural gene inheritance, this process involves collecting and processing heritage data. Chinese cultural heritage will be safeguarded, communicated, and promoted using cultural genetic visualization techniques. This technique has the potential to preserve tangible heritage, as demonstrated by Zhuxian Town Woodblock New Year prints. By visualizing and preserving China’s cultural heritage, the results contribute to understanding and engagement with its diverse culture. Heritage can be protected and added value to future generations through cultural genetic visualization techniques.